Understanding occupational and organizational psychology - Millward, Lynne (SAGE, 2005)
Provides excellent coverage of the main areas of industrial, work and organizational psychology. All main topics at the individual an group levels are covered a highly competent, research based introductory text' - Professor Neil Anderson, University of Amsterdam. The text provides comprehensive coverage of the British Psychological Society's training requirements for becoming a chartered occupational psychologist, yet it is also compliant with European training guidelines for industrial, work and organizational psychology too.- Resumé vydavatel